On the relation of quark confinement and chiral symmetry breaking - Braun, Jens; Haas, Lisa Marie; Marhauser, Florian; Pawlowski, Jan M. (Arxiv, 2009)
We study the phase diagram of QCD with the help of order parameters for chiral symmetry breaking and quark confinement. We also introduce a new order parameter for the confinement phase transition, which is related to the quark density. It is easily accessible by different theoretical approaches, such as functional approaches or lattice simulations. Its relation to the Polyakov loop expectation value is discussed and the QCD phase diagram is analysed. Our results suggest a close relation between the chiral and the confinement phase transition.
Gesehen am 05.12.2017